2017
DOI: 10.3897/zse.93.11602
|View full text |Cite
|
Sign up to set email alerts
|

A new genus of Parastenocarididae (Copepoda, Harpacticoida) from the Tocantins River basin (Goiás, Brazil), and a phylogenetic analysis of the Parastenocaridinae

Abstract: Eirinicaris antonioi gen. et sp. n. (Parastenocaridinae) is described from the Brazilian rocky savannas, an ecosystem under heavy anthropogenic pressure. The subfamily is distributed worldwide, with representatives in Africa, Asia, Australia, Europe, and North America. This is the first time a non-Remaneicaris Parastenocaridinae is described from a Neotropical region indicating that Parastenocaridinae species were already present in a vast geographical area, before the split of the Gondwana. The new taxon is i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…nov. and the other including all the analysed Stammericaris spp. Our data confirm what was reported in a recent phylogenetic analysis of all the genera included in the subfamily Parastenocaridinae(Corgosinho et al 2017), where Cottarellicaris and Stammericaris are reported as a monophyletic separate group within the subfamily. The relationships among the analysed Stammericaris spp.…”
supporting
confidence: 92%
“…nov. and the other including all the analysed Stammericaris spp. Our data confirm what was reported in a recent phylogenetic analysis of all the genera included in the subfamily Parastenocaridinae(Corgosinho et al 2017), where Cottarellicaris and Stammericaris are reported as a monophyletic separate group within the subfamily. The relationships among the analysed Stammericaris spp.…”
supporting
confidence: 92%
“…21 ). The values of Ci and Ri indices were generally low compared with previous phylogenetic studies of benthic harpacticoids that showed high rates of convergence within the taxon group ( e.g ., Karanovic & Hancock, 2009 ; Karanovic, Kim & Lee, 2015 ; Corgosinho et al, 2017 ). In both most parsimonious cladograms, the monophyly of Bicorniphontodes was supported, with a 100% bootstrap value indicating the well-defined ingroup by five unambiguous synapomorphies ( Table 1 ): hyaline frills of free body somites are serrate or crenate (character no.…”
Section: Resultsmentioning
confidence: 99%
“…This condition is present in Fontinalicaridinae and Parastenocaridinae (see Ranga Reddy et al, 2014, fig. 9 andCorgosinho et al, 2017b). However, the spinules present in Santaremicaris gen. nov. are longer and more numerous than in other Neotropical species.…”
Section: Murunducarismentioning
confidence: 95%
“…To our knowledge, such armature was never described for a Fontinalicaridinae species, occurring convergently only in some groups of species within the Parastenocaridinae. When a seta occurs on the inner margin of the P1 basis within Parastenocarididae, it is not dimorphic in shape, differing at most in length (e.g., Eirinicaris antonioi Corgosinho, Schizas, Previattelli, Rocha and Santos-Silva, 2017b). The absence of a modified medial spine in the male P1 basipodite is considered a synapomorphy for Psammonitocrella Huys, 2009 andParastenocarididae (see Martínez Arbizu andMoura, 1994;Corgosinho et al, 2020), and is a condition present in the ground pattern of the Fontinalicaridinae.…”
Section: A New Amazonian Genus Of Parastenocarididaementioning
confidence: 99%
See 1 more Smart Citation